Nitric oxide involvement in additive antidepressant-like effect of agmatine and lithium in mice forced swim test. (August 2018) - Ostadhadi, Sattar; Norouzi-Javidan, Abbas; Nikoui, Vahid; Zolfaghari, Samira; Moradi, Abouzar; Dehpour, Ahmad Reza
Highlights: Co-administration of subeffective doses of agmatine and lithium shows antidepressant-like effect in mice forced swim test. This additive effect of lithium and agmatine is mediated through nitric oxide system. Constitutive nitric oxide synthase plays a dramatic role in this response. Abstract: Lithium is still the main agent in the management of mood disorders such as depression. Likewise, agmatine protects the central nervous system (CNS) against depression. The aim of the present study was to examine the possible additive antidepressant-like effect of agmatine and lithium in mice forced swim test (FST) as well as exploration of the probable involvement of nitric oxide (NO) pathway in this response. Results showed that pretreatment with a subeffective dose of agmatine (0.01 mg/kg) augmented the antidepressant-like effect of lithium subeffective dose (3 mg/kg) ( P < 0.001). L -NG-nitroarginine methyl ester (L-NAME, nonspecific nitric oxide synthase [NOS] inhibitor) at doses of 10 and 30 mg/kg, and 7-nitroindazole (7-NI, neuronal NOS inhibitor) at doses of 15 and 30 mg/kg potentiated the antidepressant-like effect of the subeffective combination of lithium (3 mg/kg) and agmatine (0.001 mg/kg) ( P < 0.001, P < 0.01, respectively). However, various doses of aminoguanidine (25 and 50 mg/kg, inducible NOS inhibitor) failed to alter the immobility time of the same combination ( P > 0.05). Moreover, pretreatment with subeffective doses of L -arginine (substrate for NOS, 300 and 750 mg/kg) reversed the augmenting antidepressant-like effect of agmatine (0.01 mg/kg) on lithium (3 mg/kg) ( P < 0.001). Our results revealed that agmatine enhances the antidepressant-like effects of lithium and the NO pathway might mediate this phenomenon. In addition, constitutive NOS plays a dramatic role in this response. Graphical abstract: Image, graphical abstract